Lignases Production and Partial Purification of Mnp from Brazilian Fungal Isolate in Submerged Fermentation - Marti, Ferhan; Leao, Alcides Lopes [UNESP]; Melo, Itamar S de; Yan, Norman D.; Sain, Mohini (OMICS International, 2012)
The potential of ligninases as a green tool for effective valorization of lignin can be shown through enzymatic cocktails containing different lignin degrading enzymes. The present study deals with the screening of potential fungal strains useful for the liquefaction of bark containing lignin. Three different local isolates (Pleurotus ostreatus POS97/14, Pycnoporus sanguineus and the local isolated fungal strain) were selected out of ten different strains for ligninases production. Maximum production of enzymes was observed in the local isolated fungal strain after ten days in submerged fermentation. The isolated fungal strain produces ligninases mainly for manganese peroxidase (MnP). The enzyme oxidized a variety of the usual MnP substrates, including lignin related phenols. Furthermore, the partial purification for MnP was determined by FPLC and the molecular weight was evaluated by SDS-PAGE.
Keywords: Ligninases; Fungal strain; Pleurotus ostreatus; P. sanguineus; Submerged fermentation, Fast protein liquid chromatography; Manganese peroxidase; Lignin peroxidase; Lcc; Time course studies